Solving the problem of the informatization of education in the foreign countries - Mariia Verkalets (Vasyl Stefanyk Precarpathian National University, 2017)
The article is devoted to issue of informatization of education. It analyzes experience offoreign countries in solvingusing the Information and Communication Technology (ICT) in theeducational procces. I iti sout lined modern tendencies of informatization of educationinUkraine. Key words: informatization of education, Information and Communication Technology(ICT), information environment.